Legal Regulations for Anticipating Artificial Intelligence-Based Workers through Institutional Transformation of Job Training and the Human Resources Revolution - Santoso, Imam Budi; Triyunarti, Wiwin; Farhani, Athari; Azizah, Faiqah Nur; Suherman, Ade Maman (Devotion : Journal of Research and Community Service, 2024)
The rapid development of artificial intelligence (AI) technology has brought great changes to the lives of mankind. The emergence of AI as part of the rapid evolution of digitas technology has led to major changes in the world's lives. This research examines the impact of AI digitalization on Indonesia's workforce and the role of regulation in mitigating negative impacts. It emphasizes the need for holistic evaluation of labor law and modernization of professional job training programs. The research results show that the use of AI in Indonesia is increasing in various sectors, including the employment sector. Moreover, data privacy protection is still inadequate to ensure data protection and privacy of AI technology users. Therefore, it is necessary to update and add regulations that regulate comprehensively, covering data protection, algorithm transparency, occupational safety and health, elimination and specific retraining related to AI, and labor rights relevant to technological developments. It is also necessary to implement new regulations that provide legal protection for the application of AI can minimize the occurrence of cybercrimes on customer data.